Keterampilan Berpikir Kritis Dan Antusiasme Siswa Dalam Pembelajaran Berbasis Virtual Untuk Mata Kuliah Termodinamika - Fenno Farcis; Enny Wijayanti; Gunarjo Suryanto Budi; Pri Ariadi Cahya Dinata (FKIP Universitas Palangka Raya, 2021)
This study aims to determine the critical thinking skills and enthusiasm of prospective physics educator students in learning virtual-based thermodynamics courses. This type of research is a survey research that begins with the development of research instruments using a 4-D development model according to Thiagarajan consisting of 4 stages, namely: define, design, develop, and disseminate. The research subjects were 20 students of the physics education study program at the University of Palangka Raya in the Thermodynamics class. Collecting data using validation methods, evaluation techniques and student enthusiasmquestionnaires. Quantitative data were obtained from the results of critical thinking skills assessment and student enthusiasm questionnaires in the virtual-based thermodynamics learning process given at the end of the lesson. The data analysis technique used quantitative and qualitative descriptive inferential statistical test analysis. The results obtained are the test instrument for critical thinking skills learning outcomes and student enthusiasm questionnaire instruments in virtual-based thermodynamic learning that have been developed are included in the valid criteria, with Cronbach's Alpha reliability () 0.712 < 0.899 which is included in the high reliability criteria; 1) students' critical thinking skills are 87% with an average N-gain of 0.86 critical thinking skills which is in the high criteria; 2) student enthusiasm on average 91.7% students feel enthusiastic about thermodynamics learning that is carried out virtually, which can be seen from the aspect of student's intention to take part in learning by 95%, aspect of goal 90%, aspect of self-potential by 90% and positive thinking aspect by 91.7%.